Recovery from Proactive Semantic Interference in Mild Cognitive Impairment and Normal Aging: Relationship to Atrophy in Brain Regions Vulnerable to Alzheimer's Disease. - Loewenstein, David A; Curiel, Rosie E; Wright, Clinton; Sun, Xiaoyan; Alperin, Noam; Crocco, Elzabeth; Czaja, Sara J; Raffo, Arlene; Penate, Ailyn; Melo, Jose; Capp, Kimberly; Gamez, Monica; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is growing evidence that proactive semantic interference (PSI) and failure to recover from PSI may represent early features of Alzheimer's disease (AD). OBJECTIVE: This study investigated the association between PSI, recovery from PSI, and reduced MRI volumes in AD signature regions among cognitively impaired and unimpaired older adults. METHODS: Performance on the LASSI-L (a novel test of PSI and recovery from PSI) and regional brain volumetric measures were compared between 38 cognitively normal (CN) elders and 29 older participants with amnestic mild cognitive impairment (MCI). The relationship between MRI measures and performance on the LASSI-L as well as traditional memory and non-memory cognitive measures was also evaluated in both diagnostic groups. RESULTS: Relative to traditional neuropsychological measures, MCI patients' failure to recover from PSI was associated with reduced volumes in the hippocampus (rs = 0.48), precuneus (rs = 0.50); rostral middle frontal lobules (rs = 0.54); inferior temporal lobules (rs = 0.49), superior parietal lobules (rs = 0.47), temporal pole (rs = 0.44), and increased dilatation of the inferior lateral ventricle (rs = -0.49). For CN elders, only increased inferior lateral ventricular size was associated with vulnerability to PSI (rs = -0.49), the failure to recover from PSI (rs = -0.57), and delayed recall on the Hopkins Verbal Learning Test-Revised (rs = -0.48). DISCUSSION: LASSI-L indices eliciting failure to recover from PSI were more highly associated with more MRI regional biomarkers of AD than other traditional cognitive measures. These results as well as recent amyloid imaging studies with otherwise cognitively normal subjects, suggest that recovery from PSI may be a sensitive marker of preclinical AD and deserves further investigation.

Life's Simple 7's Cardiovascular Health Metrics are Associated with Hispanic/Latino Neurocognitive Function: HCHS/SOL Results. - González, Hector M; Tarraf, Wassim; Gouskova, Natalia; Rodríguez, Carlos J; Rundek, Tatjana; Grober, Ellen; Pirzada, Amber; González, Patricia; Lutsey, Pamela L; Camacho, Alvaro; Daviglus, Martha L; Wright, Clinton; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Hispanics/Latinos are purportedly at increased risk for neurocognitive decline and dementias. Without dementia cures, low-cost, well-tolerated public health means for mitigating neurocognitive decline are needed. OBJECTIVE: We examined associations between neurocognition and cardiovascular health (CVH) metrics (Life's Simple 7; LS7) among diverse Hispanics/Latinos. We hypothesized that higher LS7 would be associated with healthier brain function (neurocognitive performance). METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; N = 9,623; ages 45-74 years) to examine neurocognition in relation to CVH LS7 scores. RESULTS: In age and sex adjusted models, a one unit LS7 score increase (range = 0-14) was associated with higher neurocognitive function on the B-SEVLT sum (0.23 [p < 0.01]; range = 3-42), B-SEVLT recall (0.12 [p < 0.01]; range = 0-15), Word Fluency (phonemic; 0.46 (p < 0.01); range = 0-49), and Digit Symbol Substitution (0.49 (p < 0.01); range = 0-83) tests, respectively. Stated differently, a change from the minimum LS7 (0) to maximum LS7 (14) score corresponded to higher scores on verbal learning (4.62) and memory (2.24), verbal fluency (7.0), and psychomotor processing speed (12). In fully adjusted models the associations were attenuated, but remained statistically significant. Incremental adjustments indicated that Latino background and, to a lesser extent, education were primary contributors to the evinced attenuations. CONCLUSIONS: We found that higher neurocognitive function was associated with better LS7 CVH metrics among middle-aged and older Hispanics/Latinos. Associations between neurocognitive function and LS7 were strongest among two at-risk groups for neurocognitive decline and dementia, women and Hispanics/Latinos with lower education. Public health efforts to reduce cardiovascular disease morbidity and mortality may have additional neurocognitive benefits among at-risk Hispanics/Latinos.